2011
DOI: 10.1074/jbc.m110.175463
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Tyrosylprotein Sulfotransferase-2 Activity Results in Altered Sperm-Egg Interactions and Loss of ADAM3 and ADAM6 in Epididymal Sperm

Abstract: Tyrosine O-sulfation is a post-translational modification catalyzed by two tyrosylprotein sulfotransferases (TPST-1 and TPST-2) in the trans-Golgi network. Tpst2-deficient mice have male infertility, sperm motility defects, and possible abnormalities in sperm-egg membrane interactions. Studies here show that compared with wild-type sperm, fewer Tpst2-null sperm bind to the egg membrane, but more of these bound sperm progress to membrane fusion. Similar outcomes were observed with wild-type sperm treated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 57 publications
0
43
0
Order By: Relevance
“…The GPIase activity of tACE (i.e., the release of glycosylphosphatidylinositol-anchored proteins from the membrane) is implicated in ADAM3 modification during epididymal maturation (32). In addition to tissue-specific factors, recent studies indicated that the ubiquitously expressed proteins, TPST2 (protein-tyrosine sulfotransferase 2) and INPP5B (inositol polyphosphate-5-phosphatase B), are involved in ADAM3 quality control (13,33). Although aberrant folding and modification in cells can be associated with pathological conditions, including amyloid diseases such as Parkinson and Alzheimer's diseases (34,35), the complex relationships between different quality control systems in vivo is not fully understood (36).…”
Section: Discussionmentioning
confidence: 99%
“…The GPIase activity of tACE (i.e., the release of glycosylphosphatidylinositol-anchored proteins from the membrane) is implicated in ADAM3 modification during epididymal maturation (32). In addition to tissue-specific factors, recent studies indicated that the ubiquitously expressed proteins, TPST2 (protein-tyrosine sulfotransferase 2) and INPP5B (inositol polyphosphate-5-phosphatase B), are involved in ADAM3 quality control (13,33). Although aberrant folding and modification in cells can be associated with pathological conditions, including amyloid diseases such as Parkinson and Alzheimer's diseases (34,35), the complex relationships between different quality control systems in vivo is not fully understood (36).…”
Section: Discussionmentioning
confidence: 99%
“…Trimeric complexes between ADAM2-ADAM3-ADAM4, ADAM2-ADAM3-ADAM5, and ADAM2-ADAM3-ADAM6 have also been described [ 56 ]. Interestingly, ADAM3 and ADAM6 are lost from spermatozoa in mice lacking tyrosylprotein sulfotransferase-2 activity, which catalyzes the post-translational modifi cation of tyrosine O-sulfation, suggesting additional PTM of ADAM proteins contribute to their functionality or quality control [ 57 ]. Tyrosine O-sulfation has been shown in other cell systems to play a role in protein complex formation [ 58 ].…”
Section: Protein Processingmentioning
confidence: 92%
“…81 Levels of ADAM18, ADAM24, ADAM26, and ADAM32, on the other hand, remain unchanged in Adam2 -/-and Adam3 -/-testicular cells and mature sperm. 64,66 The significant reductions in ADAM protein levels that have been reported in knockout mouse sperm are unsurprising given the various ADAM complexes that exist in mature sperm and the fact that many ADAMs are degraded if they are unable to form complexes with other ADAMs (Figure 2).…”
Section: Reviewsmentioning
confidence: 92%
“…98 In relation to ADAM3 expression in sperm, it should be noted that male mice with deletions in Ace (encodes angioten-converting enzyme [ ) genes are infertile, and ADAM3 is commonly absent or defective in mature sperm from these mutant mice. 81,85,[99][100][101] The spermatogenesis-specific chaperone CLGN is required for the formation of the ADAM1A-ADAM2 complex, which regulates the integrity of ADAM3. 100,102 The testis-specific calreticulin-like chaperone CALR3, testis-specific protein disulfide iso merase homolog PDILT, and tyrosine-O-sulfation-catalyzing enzyme TPST2 are critical for the stability of ADAM3.…”
Section: Role Of Adams In Fertilizationmentioning
confidence: 99%